Dostoevsky and Bakhtin - STEPANYAN, KAREN (Bulletin of Yerevan University H: Russian Philology, 2021)
In defiance of Bakhtin’s opinion that carnavalization is among the main categories of Dostoevsky’s artistic world, author of this article supposes, that from “The Poor Folks” till “The Brothers Karamazov” Dostoevsky was preoccupied with not breaking the hierarchical system of human life but its restoration, not masquerade, but revealing the true essence of a man, not the profanation of sacred scriptures but the detection of their main ideas, not the inversion of the world, but the representation of true reality. How the formalistic method influenced Bakhtin’s works and how to combine the freedom of Dostoevsky’s personages with the author’s intention is also a question of this article.